1995
DOI: 10.1159/000244253
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Biochemical Forms of Transforming Growth Factor-α Present in Human Milk and Secreted by Human Milk Macrophages

Abstract: Objective: Transforming growth factor-α (TGF-α), present in human milk, is thought to play a significant role in postnatal gut development. Macrophages, which abound in human milk, are known to secrete various isoforms of TGF-α in other areas of the body. It was hypothesized that human milk macrophages (HMM) secrete TGF-α, and HMM are a source of TGF-α isoforms present in human milk. We sought to measure in vitro HMM TGF-α secretion, and to compare the TGF-α isoform(s) present in human milk with those secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The absence of these higher molecular mass isoforms from later postnatal age AM media samples, the minimal staining of rainbow molecular mass markers, and negative secondary control support the premise that these isofoms are true TGFa-like moieties reacting with the TGFa MAb. Similar higher molecular mass TGFa isoforms have been identified in the medium of human milk macrophages in our laboratory with only the 6-kD isoform identified in human milk supernatant (42). It appears, therefore, that higher molecular mass isoforms >22 kD are secreted by AM and may represent aggregation at disulfide bonds, or as yet, another unidentified member of the EGF family with structural homology to TGFa.…”
Section: Discussionsupporting
confidence: 78%
“…The absence of these higher molecular mass isoforms from later postnatal age AM media samples, the minimal staining of rainbow molecular mass markers, and negative secondary control support the premise that these isofoms are true TGFa-like moieties reacting with the TGFa MAb. Similar higher molecular mass TGFa isoforms have been identified in the medium of human milk macrophages in our laboratory with only the 6-kD isoform identified in human milk supernatant (42). It appears, therefore, that higher molecular mass isoforms >22 kD are secreted by AM and may represent aggregation at disulfide bonds, or as yet, another unidentified member of the EGF family with structural homology to TGFa.…”
Section: Discussionsupporting
confidence: 78%
“…Okada et al (18) verified TGF-␣ concentration in human milk using a specific RIA assay. Wagner et al (29) have found that human milk contains different biochemical forms of TGF-␣ that can originate from human milk macrophage secretion. Results from these studies have shown that TGF-␣ concentration in mature milk is markedly lower compared with EGF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Human milk samples were placed in 4°C then processed within 8 h of expression. Milk was spun at 1,000 g for 25 min at 4°C to achieve separation of the cellular, fat and aqueous compartments of human milk as previously described [26]. Following separation, the AHM samples were frozen at -20°C until further testing.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages were isolated from whole human milk according to the methods previously reported [26]. Isolated macrophages were placed in culture at a concentration of 1 !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation